Anti-crime package and drug policy in Brazil under the Bolsonaro government - Quadrado, Jaqueline Carvalho (Argumentum, 2025)
This text analyses measures taken by the Bolsonaro government, specifically: the Anti-Crime Package and Law nº 13,840, of June 5, 2019, which instituted the New National Drug Policy. It identifies the use of crime as a strategic issue, especially for political purposes, as a way of earning positive evaluations of the government by the population. It also recognises the use of fear and a sense of insecurity as elements to justify the removal of fundamental rights, through the enactment of more onerous laws and increased control, as witnessed in daily city-life.